2014
DOI: 10.1111/medu.12385
|View full text |Cite
|
Sign up to set email alerts
|

Expertise under the microscope: processing histopathological slides

Abstract: This study indicates that in the case of intermediates and experts, different visual and cognitive strategies can result in equal levels of diagnostic accuracy. Lessons for training underline the relevance of the distinction between normal and abnormal tissue for novices, especially when the mental rotation of 2-D images is required. Intermediates need to be trained to see deviations in abnormalities. Feedback and an educational design that is specific to these developmental stages might improve training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…We fully agree with that, but would like to point towards research not mentioned by these authors, i.e., by Bertram, Helle, Kaakinen, and Svedström (2013) on CT images and our own research on interactive digital pathology slides (Jaarsma et al, 2016;Jaarsma, Jarodzka, Nap, Van Merriënboer, & Boshuizen, 2015;Jaarsma et al, 2014) and on patient-video cases (Balslev et al, 2012). Moreover, the authors mention on several occasions the potential eye tracking has for medical education.…”
Section: Eye Trackingmentioning
confidence: 83%
See 3 more Smart Citations
“…We fully agree with that, but would like to point towards research not mentioned by these authors, i.e., by Bertram, Helle, Kaakinen, and Svedström (2013) on CT images and our own research on interactive digital pathology slides (Jaarsma et al, 2016;Jaarsma, Jarodzka, Nap, Van Merriënboer, & Boshuizen, 2015;Jaarsma et al, 2014) and on patient-video cases (Balslev et al, 2012). Moreover, the authors mention on several occasions the potential eye tracking has for medical education.…”
Section: Eye Trackingmentioning
confidence: 83%
“…Manipulation of these hypotheses can lead to the non-recognition of such features (Brooks, LeBlanc, & Norman, 2000;LeBlanc, Brooks, & Norman, 2002;LeBlanc, Dore, Norman, & Brooks, 2004;LeBlanc, Norman, & Brooks, 2001). The alleged superficiality of our own analyses of verbal protocols turned out to reveal aspects of perception and cognition (Jaarsma et al, 2014) that we have never become aware of in earlier research that made use of deep, semantic analyses (see for instance, Boshuizen & Schmidt, 1992). Lack of a professional vocabulary in novice groups seems to be associated with a lack of a repertoire of perceptual features in that domain thus hampering perception and interpretation.…”
Section: Verbalisations -The Working Memory Outputmentioning
confidence: 99%
See 2 more Smart Citations
“…For educational purposes, this might be another argument in favor of digital pathology in daily practice. Other studies [7] have shown that registration of eye movements on screen during examination of digital histology slides also reflect the level of experience from the observer. Apparently, digital histology can also play an important role in objectivizing the performance of the apprentice.…”
Section: Discussionmentioning
confidence: 99%